Предмет: Алгебра,
автор: stark665754
а)
12a² b+8ab²
------------------
9a²-4b²
б)
36c²-60c+25
--------------------
25-36с²
Ответы
Автор ответа:
0
а) (12a^2 *b + 8ab^2)/ (9a^2 - 4b^2) = 4ab(3a+2b)/((3a-2b)(3a+2b)) = 4ab / (3a-2b)
б) (36c^2 - 60c +25) / (25-36c^2) = (6c-50^2 / ((5-6c)(5+6c)) = (6c-5)^2 / (-(6c-5)(5+6c)) =
= (6c-5)/-(5+6c)
б) (36c^2 - 60c +25) / (25-36c^2) = (6c-50^2 / ((5-6c)(5+6c)) = (6c-5)^2 / (-(6c-5)(5+6c)) =
= (6c-5)/-(5+6c)
Похожие вопросы
Предмет: Английский язык,
автор: baratjan3103
Предмет: Математика,
автор: mayakovalina
Предмет: История,
автор: malcevaolesa343
Предмет: Математика,
автор: Тикирики
Предмет: Алгебра,
автор: lerik12345